2018
DOI: 10.1111/apm.12887
|View full text |Cite
|
Sign up to set email alerts
|

Performance characteristics of newer MIC gradient strip tests compared with the Etest for antimicrobial susceptibility testing of Neisseria gonorrhoeae

Abstract: For Neisseria gonorrhoeae susceptibility testing, Etest, comparable to agar dilution, is frequently used. In recent years, newer MIC gradient strip tests have been commercialized. However, these tests have not been appropriately evaluated for gonococci. We evaluated the sensitivity, specificity, accuracy, quality, availability of antimicrobials and cost of the MIC Test Strip (Liofilchem), M.I.C.Evaluator (Oxoid) and Ezy MIC Strip (HiMedia), compared to the reference Etest (bioMérieux), for gonococcal susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
(48 reference statements)
1
14
0
Order By: Relevance
“…However, the mean and modal MICs obtained by both gradient strip methods were higher than those determined by the agar dilution MIC method. In consequence, agreement between the two gradient strip methods was higher (88%) than that obtained for each method compared with the agar dilution MIC method, consistent with a previous study which found good agreement when comparing the Etest and the MIC test strip (7). This finding is notable as it suggests that future comparison studies of gradient MIC strips should continue to include the agar dilution MIC method as the reference method.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, the mean and modal MICs obtained by both gradient strip methods were higher than those determined by the agar dilution MIC method. In consequence, agreement between the two gradient strip methods was higher (88%) than that obtained for each method compared with the agar dilution MIC method, consistent with a previous study which found good agreement when comparing the Etest and the MIC test strip (7). This finding is notable as it suggests that future comparison studies of gradient MIC strips should continue to include the agar dilution MIC method as the reference method.…”
Section: Discussionsupporting
confidence: 87%
“…gonorrhoeae, but it is labor intensive, is time consuming, and does not present results in a clinically relevant time frame (5). There are now several azithromycin gradient MIC strips available, and the limited comparison studies available demonstrate promising equivalence of these methods (5)(6)(7).…”
mentioning
confidence: 99%
“…Therefore, though the MICs estimated by different laboratories are comparable, their values may vary by one or more twofold dilution due to slight technical differences, hence affecting the clinical interpretation 37. In terms of the E-test method, it is costly, requiring the use of experimental materials that are very expensive because of manufacturer’s patent protection, and these materials were not available in some areas 38. On the other hand, the molecular assays (PCR and WGS) detecting the mutation A2059G could be an alternative method for identifying isolates with high-level azithromycin resistance; however, they have not been developed into a commercial diagnostic kit for clinical use nowadays.…”
Section: Discussionmentioning
confidence: 99%
“…Agar dilution for quantitative determination has been replaced by the minimal inhibitory concentration (MIC) gradient strip test methodology in the last years. This is an easier and less time consuming method providing precise and reliable results [13]. However, MIC gradient strip tests are more costly than classical, less accurate test methods such as disc diffusion techniques.…”
Section: Introductionmentioning
confidence: 99%
“…For a few years now, different companies have been offering MIC strip tests for antibiotic susceptibility testing. However, it has been demonstrated that the choice of gradient strip test manufacturers can influence testing outcomes [13], as do bacterial growth conditions, i.e. the choice of media or pH [9].…”
Section: Introductionmentioning
confidence: 99%